2008
DOI: 10.1002/chir.20627
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and supramolecular chirality: R2PI spectroscopy as a tool for the gas‐phase recognition of chiral systems of biological interest

Abstract: Dedicated to Professor Domenico Misiti on the occasion of his 75th birthday. ABSTRACTIn life sciences, diastereomeric chiral molecule/chiral receptor complexes are held together by a different combination of intermolecular forces and are therefore endowed with different stability and reactivity. Determination of these forces, which are normally affected in the condensed phase by solvent and supramolecular interactions, can be accomplished through the generation of diastereomeric complexes in the isolated state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 133 publications
(159 reference statements)
1
14
0
Order By: Relevance
“…High-repetition lasers therefore are particularly useful for CD-LAMS. A further measure is to increase the laser pulse energies in addition to an increase of laser-beam width in such a way that the laser power density (energy per second and cm 2 ) is kept constant. This results in a larger volume of overlap between laser beam and molecular beam and therefore gives rise to larger ion numbers per laser pulse.…”
Section: Reduction Of the Influence Of Single Pulse And Long-term Flumentioning
confidence: 99%
See 1 more Smart Citation
“…High-repetition lasers therefore are particularly useful for CD-LAMS. A further measure is to increase the laser pulse energies in addition to an increase of laser-beam width in such a way that the laser power density (energy per second and cm 2 ) is kept constant. This results in a larger volume of overlap between laser beam and molecular beam and therefore gives rise to larger ion numbers per laser pulse.…”
Section: Reduction Of the Influence Of Single Pulse And Long-term Flumentioning
confidence: 99%
“…On the other hand, the investigation of electronic properties and conformation of chiral molecules is of fundamental importance for the understanding of these enantio-specific natural processes and the development of methods of asymmetric synthesis, in particular of catalytically enhanced ones. In this context, chiral recognition in the gas phase [1][2][3][4] is of special interest. One very useful tool for analysis as well as for scientific investigation of chiral molecular systems in the condensed or in the gas phase is circular dichroism spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sensitive gas-phase experiments are suitable for their detection in isolated tailor-made molecular clusters. 26,29,30 For example, mass spectrometry revealed the extraordinary self-organization of homochiral protonated serine (Ser) tetramers 4 and octamers, [31][32][33] that were hereupon presented as a possible origin for biomolecular homochirality. 34 A recent gasphase vibrational spectroscopy study revealed an asymmetric, yet highly H-bonded structure for the Ser 8 H + magic number cluster.…”
Section: Introductionmentioning
confidence: 99%
“…21,[37][38][39][40] In the same context, a change of chirality of a residue within one peptide chain, or of one of the complexation partners within a complex of chiral molecules, results in a structural change, which is easily evidenced from spectroscopy. 22,[41][42][43][44][45][46][47][48] The nature of the change ranges from subtle differences in dispersion forces between the homochiral and heterochiral complexes 49,50 to a drastic rearrangement of the binding pattern (OHÁ Á ÁO vs. OHÁ Á ÁN interaction, or hydrogen bond vs. dispersion). [51][52][53] In many cases, the difference between two diastereomeric interacting pairs rests on delicate interactions like CHÁ Á Áp or CHÁ Á ÁO interactions, which are much weaker than the main interactions ensuring the stability of the complex.…”
Section: Introductionmentioning
confidence: 99%